Newbury, Wabaunsee County - Haynos, Thomas (Kansas State University, The Chapman Center for Rural Studies, 2011)
The land was bought from the Pottawatomie Indians by the Atchison, Topeka, and Santa Fe Railroad and sold to German immigrants for a profit. The township of Newbury was established in 1868, and the town bearing the same name followed soon after. The towns history follows a series of disappointments of poor water source, lost county seat, and the railroad bypassing them. The Catholic Church remains in service to the rural area.
Thomas Haynos, “Newbury, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/20.
Keywords: Mulberry Creek; Newbury; P.H. Moser; Topeka Atchison Santa Fe Railroad; Wabaunsee County; Thomas Haynos